Faujasites exchanged with alkylammonium cations applied to basic catalysis - Almeida, Karina Arruda; Hammer, Peter [UNESP]; Cardoso, Dilson (Elsevier B.V., 2019)
NaX and NaY faujasites (with Si/Al ratios of 1.3 and 2.5, respectively) were subjected to different degrees of ionic exchange with linear monoalkylammonium cations containing between 1 and 6 carbon atoms. The products were characterized using X-ray diffraction (XRD), nitrogen physisorption, X-ray photoelectron spectroscopy (XPS), and thermogravimetric analysis (TGA). The Knoevenagel condensation was used as a model reaction to characterize the activity and accessibility of the catalytic sites. Ionic exchange isotherms showed that only the sodium cations present in the supercavities were exchangeable for the alkylammonium ions. The XPS results showed that the monoalkylammonium cations increased the basicity of the sites of both faujasites, with the basicity increasing with the length of the carbon chain. The catalytic activity in the Knoevenagel condensation was governed by three factors: the degree of exchange, the aluminum content, and the water content of the zeolites.
Keywords: Zeolite; Faujasite; Ion exchange; Alkylammonium cations; Aluminum content; Basic catalyst